Regioselective electrolytic 5, 8-difluorination of quinolines. Issue 6 (6th February 2020) - Spurlin, Sean; Blocker, Mark; LoBue, James; Wu, Ji; Padgett, Clifford; Shaikh, Abid
Graphical abstract: Highlights: A regioselective incorporation of fluorine atoms on the benzenoid ring of quinolines has been developed using Olah's reagent. This method provides a direct access to difluorinated quinolines using electrolysis and ambient reaction conditions. Products obtained in moderate to good yields in short reaction time. Abstract: Electrochemical anodic oxidation method for the incorporation of fluorine atom into quinoline ring is described. Our method involves a regioselective 5, 8-difluorination of quinolines using HF:pyridine as a reagent/supporting electrolyte in an undivided electrochemical cell equipped with platinum anode and cathode. Various quinoline derivatives were subjected to electrolytic fluorination at room temperature to obtain moderate to good yields in short reaction time.